2018
DOI: 10.1371/journal.ppat.1007040
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus establishes a latent reservoir and triggers long-lasting inflammation in the eye

Abstract: Recent outbreaks of Ebola and Zika have highlighted the possibility that viruses may cause enduring infections in tissues like the eye, including the neural retina, which have been considered immune privileged. Whether this is a peculiarity of exotic viruses remains unclear, since the impact of more common viral infections on neural compartments has not been examined, especially in immunocompetent hosts. Cytomegalovirus is a common, universally distributed pathogen, generally innocuous in healthy individuals. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 46 publications
1
27
0
Order By: Relevance
“…A myeloid cell niche has been proposed as a common mechanism for viral persistence in other infections such as Dengue, Chikungunya and Marburg virus (7). In the case of DNA viruses such as CMV, viral targeting of myeloid cells is a prominent mechanism for achieving latent infection (20).…”
mentioning
confidence: 99%
“…A myeloid cell niche has been proposed as a common mechanism for viral persistence in other infections such as Dengue, Chikungunya and Marburg virus (7). In the case of DNA viruses such as CMV, viral targeting of myeloid cells is a prominent mechanism for achieving latent infection (20).…”
mentioning
confidence: 99%
“…However, there have been con icting reports regarding whether MCMV can undergo ocular latency following systemic infection, with several studies reporting that immunosuppression is required for intraocular viral replication after systemic MCMV infection 23,43,44 while others have reported that MCMV DNA could not be detected within eye tissues of immunocompetent adult C57BL/6 mice several months post systemic MCMV infection 20 . A study by Bale et al reported that latent ocular MCMV could be detected in 10% of mice infected with MCMV via the intraperitoneal route 45 while a recent study from Voigt et al 46 showed that MCMV spread to the eye following i.p. inoculation of adult BALB/c mice with 1x10 4 PFU, resulting in latent infection in both the iris (26%) and choroid (22%).…”
Section: Discussionmentioning
confidence: 99%
“…Retinal wholemounts for CD45 and collagen IV staining followed a previously published protocol. 31 Image acquisition was done on a Nikon A1Si confocal microscope and images captured on an Andor 885 EMCCD camera with the NIS Elements imaging software.…”
Section: Tissue Processing and Immunohistochemistrymentioning
confidence: 99%
“…Data from 6-month-old mouse retinas for average GFP + cell quantification were obtained after the papain dissociation protocol (minimum of n = 5 per mouse line). The trypsin and liberase protocols were taken from previously published studies, 31,33,34 while the papain protocol was adapted from Barber et al 35 as follows. Freshly dissected retinal sample were incubated in a 1:20 solution of papain/DNase (Worthington Biochemicals, LK003176/LK003170) at 37°C for 45min and gently triturated.…”
Section: Cell Dissociation and Flow Cytometry Analysismentioning
confidence: 99%